2023
DOI: 10.26719/emhj.23.029
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 syndrome among healthcare workers in Jordan

Abstract: Background: Post-COVID-19 syndrome covers a wide range of new, recurring or ongoing health conditions, which can occur in anyone who has recovered from COVID-19. The condition may affect multiple systems and organs. Aims: To evaluate the frequency and nature of persistent COVID-19 symptoms among healthcare providers in Jordan. Methods: Post-COVID-19 syndrome refers to symptoms extending beyond 4–12 weeks. We conducted a historical cohort study among 140 healthcare staff employed at the National Center for Diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Finally, females were more likely to report long COVID-19 in the present study. This is in line with the open literature, consistently showing that the risk of long COVID-19 is higher in females [ 4 , 10 , 15 , 45 , 46 , 47 ]. Although hormone-dependent mechanistic hypotheses have been proposed, sex-dependent self-reporting bias shall not been ruled out either, considering the fact that sex-dependent discrepancy in medical care already existed long before the pandemic [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…Finally, females were more likely to report long COVID-19 in the present study. This is in line with the open literature, consistently showing that the risk of long COVID-19 is higher in females [ 4 , 10 , 15 , 45 , 46 , 47 ]. Although hormone-dependent mechanistic hypotheses have been proposed, sex-dependent self-reporting bias shall not been ruled out either, considering the fact that sex-dependent discrepancy in medical care already existed long before the pandemic [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the same vein, fatigue was the most reported symptom among Jordanian HCWs [24]. These results opined that most PCC manifestations were ongoing COVID-19 symptoms.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, Osikomaiya et al [23] observed that 12.8% of patients with PCC in Nigeria had persistent fatigability and another 12.8% had a headache after their discharge from the hospital. In the same vein, fatigue was the most reported symptom among Jordanian HCWs [24]. These results opined that most PCC manifestations were ongoing COVID-19 symptoms.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, Hyassat D, et al [24] reported that 59.3% of the healthcare providers in Jordan reported more than one persisting COVID-19 symptom, and among them, 97.5%, 62.6%, and 40.9% reported more than one COVID-19 symptom at 1-3, 3-6 and 6-12 months, respectively, after the acute phase of the infection. This finding is in consonant with our findings.…”
Section: Discussionmentioning
confidence: 99%